UPAYA HUKUM ACTIO PAULIANA DALAM MELINDUNGI KREDITOR ATAS ASET DEBITOR DALAM KEPAILITAN PERSEROAN TERBATAS - Ruben Tambunan; Sunarmi Sunarmi; Dedi Harianto; Suhaidi Suhaidi (Universitas Sumatera Utara, 2017)
ABSTRACT The legal action of Actio pauliana in the bankruptcy of a limited liability company is the cancellation of a legal act of transferring the company’s assets to a third party by the debtor (in bankcruptcy) where such action is not obliged to do (the existence of bad faith), this harming the creditor as refrred to in Articles 41 to 47 of Law Number 37 of 2004 concerning Bankruptcy and Suspension of Obligation of Debt Payment. The legal action of Actio pauliana is to provide legal protection and legal certainty to the creditors for the repayment of the debts of the debtor. The application for the cancellation of this legal act shall be submitted to the Commercial Court by a designated and appointed curator by a court assigned to conduct the management and/or ordering of property from a bankrupt party. The important thing to be noticed before such petition is submitted to the Comercial Court is to ensure that the ownership of the asset is actually on behalf of the company so that the petition for the cancellation of such legal act is not in vain. Keywords: Bankrupttcy, Actio pauliana, Limited liability company.